The meaning of Mariah Carey - Carey, Mariah; Davis, Michaela Angela, 1964- (London Pan Books, 2020)
"Mariah Carey shares her life story"--
Half title page verso signed by Mariah Carey.
Keywords: Carey, Mariah; Singers -- United States -- Biography; Autobiographies